2012
DOI: 10.1186/1297-9686-44-19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental heterogeneity of residual variance of weight traits in Nellore beef cattle

Abstract: BackgroundMany studies have provided evidence of the existence of genetic heterogeneity of environmental variance, suggesting that it could be exploited to improve robustness and uniformity of livestock by selection. However, little is known about the perspectives of such a selection strategy in beef cattle.MethodsA two-step approach was applied to study the genetic heterogeneity of residual variance of weight gain from birth to weaning and long-yearling weight in a Nellore beef cattle population. First, an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In the case of unscaled data, the estimates of variance components were very similar for the HOM and the HET models. Neves et al (2012) also found similar estimates of variance components for HOM and HET models for body weight traits in Nellore beef cattle. After scaling data, there was a slight increase of additive genetic variances for model 3, but the increment was much bigger for model 2 (Table 4).…”
Section: Estimation Of Variance Componentssupporting
confidence: 58%
“…In the case of unscaled data, the estimates of variance components were very similar for the HOM and the HET models. Neves et al (2012) also found similar estimates of variance components for HOM and HET models for body weight traits in Nellore beef cattle. After scaling data, there was a slight increase of additive genetic variances for model 3, but the increment was much bigger for model 2 (Table 4).…”
Section: Estimation Of Variance Componentssupporting
confidence: 58%
“…where: is the vector of observations; is the regression coefficients vector of fixed trajectory of each sex; is the vector of random regression coefficients attributed to additive genetic effects; X and Z are incidence matrices of effects in b and a, containing Legendre polynomials relative to the value of the control variable adopted for the tryptophan:lysine ratio; and e is the residue vector. Several studies working with the comparison of random models using residual variance observed similar performance among the main evaluation criteria (NEVES et al, 2012, BIGNARDI et al, 2009, BREWER et al, 2016. Thus, the comparisons of homogeneous and heterogeneous models were performed via Bayesian Information Rev.…”
Section: Methodsmentioning
confidence: 86%
“…The log-transformation of the variance [31], the Box-Cox power transformation [32], or the coefficient of variation (CV) [33] are commonly used to make σ 2 independent of μ [34]. The transformed data can be compared with the log-log-test [31], the naive test [34], the likelihood ratio test, Bennett's test, the score test, Miller's test, Doornbos and Dijkstra's test or the Wald test.…”
Section: Transformationsmentioning
confidence: 99%
“…The transformed data can be compared with the log-log-test [31], the naive test [34], the likelihood ratio test, Bennett's test, the score test, Miller's test, Doornbos and Dijkstra's test or the Wald test.…”
Section: Transformationsmentioning
confidence: 99%